Research Progress in Supercritical CO2 Microchannel Heat Exchangers - Huang Junjie; Han Zengxiao; Guo Jiangfeng; Huai Xiulan (Zhileng xuebao)
In the context of the "3060 carbon peaking and carbon neutrality goals", promoting energy-efficient transportation and rational utilization is one of the important paths to achieve carbon neutrality, where heat exchangers are known to play a crucial role. Compared with traditional heat exchangers, microchannel heat exchangers significantly reduce the volume while maintaining the same heat exchange capacity. They also significantly improve the heat exchange efficiency and have applications in many important fields. For example, supercritical CO2 (S-CO2) power generation systems, transcritical heat pumps, and refrigeration systems have important application prospects as they are environmentally friendly and offer high-efficiency advantages in the context of the "dual carbon target." Drastic changes in the properties of S-CO2 and the high-temperature and high-pressure requirements of the system pose significant challenges to heat exchanger design, high-temperature and high-pressure resistance, compactness, and efficiency. Therefore, S-CO2 heat exchangers have become a hot topic in scientific and industrial research. In recent decades, significant progress has been made in related research. This paper comprehensively reviews the research progress of microchannel heat exchangers in S-CO2 systems. The paper focuses on different structural forms and design optimization methods of printed circuit heat exchangers (PCHE) and discusses the impact of PCHE optimization on the performance improvement of the entire S-CO2 system. This review provides a comprehensive discussion of S-CO2 microchannel heat exchangers and provides an important reference for the selection, design, and optimization of heat exchangers in systems using CO2 or other supercritical working fluids as the working media for power generation, heat pumps, and refrigeration.